Effectiveness of POE Learning Model on Science Process Skills in Temperature and Heat of Elementary Students - Novita Uriyah; Zainul Arifin Imam Supardi; Suryanti (Studies in Philosophy of Science and Education, 2023)
This research aims to explain the effectiveness of the Predict-Observe-Explain (POE) learning model on elementary students' science process skills on temperature and heat material. This research was conducted on fifth-grade students at SDN Kalirungkut I/264. This research method is a quasi-experiment with a non-equivalent control group research design. The data was collected through test and non-test (observation) techniques. Based on the N-Gains score test, the score in the experimental group was 58.12697%, which is quite effective. Based on the analysis using effect size on experimental and control class students, it is known that the effect size value is 1.131611, which means that learning with the POE model on temperature and heat material has a high influence on students' science process skills. Based on the results of the research conducted, it can be concluded that the POE learning model is more effective than conventional learning of scientific process skills. This research will help students improve their fundamental scientific process skills using the POE model. In prior research, no one has tried to examine the topic of temperature and heat and no one has calculated the effectiveness of the POE model on science process skills using effect size.